2001
DOI: 10.1016/s0736-0266(00)00011-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tensile stretch inhibition of nitric oxide release from osteoblast‐like cells is both G protein and actin‐dependent

Abstract: Recent reports indicate the alteration of nitric oxide (NO) synthesis with mechanical stress loaded on the osteoblast and NO is considered to have a significant role in mechanotransduction. We found the involvement of guanine-nucleotide-binding regulatory proteins (G proteins), especially Gi, in stress-inhibited NO release of osteoblast-like cells (JOR: 17393-597, 1999). To determine further the mechanism involved in this process, we measured c-Jun N-terminal kinasehtress-activated protein kinase (JNWSAPK) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…We also showed that PTX treatment inhibited A␤-induced JNK activation, suggesting that G protein activation is an upstream event in JNK activation. Our results are also consistent with reports showing that G proteins regulate JNK activity in other systems (23,24,66,67). The activation of JNK by G proteins may proceed via the interaction of G␤␥ subunits with two guanine nucleotide exchange factors including Rac1 and Cdc42 (25).…”
Section: Discussionsupporting
confidence: 92%
“…We also showed that PTX treatment inhibited A␤-induced JNK activation, suggesting that G protein activation is an upstream event in JNK activation. Our results are also consistent with reports showing that G proteins regulate JNK activity in other systems (23,24,66,67). The activation of JNK by G proteins may proceed via the interaction of G␤␥ subunits with two guanine nucleotide exchange factors including Rac1 and Cdc42 (25).…”
Section: Discussionsupporting
confidence: 92%
“…Following up the hypotonic loading response with the response to the isotonic "recovery" phase in dynamic osmotic loading may contribute to the differences in the calcium response and cytoskeleton organization for dynamic osmotic loading compared with that for static osmotic loading. Because the actin cytoskeleton has been proposed as a mechanosensor in various cell types (22,23,61), this differential actin reorganization between static and dynamic osmotic loading may lead to downstream secondary changes in cell signaling and activities (such as gene expression and cell biosynthesis, e.g., Ref. 4).…”
Section: Discussionmentioning
confidence: 99%
“…stress in bone cells in a manner that is similar to that observed in other cell types, such as muscle [ 11,361. Cyclic tensile stretch stimulates c-Jun N-terminal kinasel stress-activated protein kinase (JNKKAPK) activity in osteoblasts [13], and fluid shear enhances CAMP accumulation [33]. The net results may be phosphorylation of aB-crystallin during mechanotransduction in bone.…”
Section: Discussionmentioning
confidence: 99%
“…When osteoblasts are mechanically strained, there is a coordinated increase in the synthesis and accumulation of specific cytoskeletal and extracellular matrix proteins, including vinculin and fibronectin, followed by increased formation and thickening of actin stress fibers, dissolution of microtubules, and an increase in the number of focal adhesions [27]. The net results are changes in the shape of osteoblastic cells and alterations in their cytoskeleton during mechanotransduction [1, 13,34]. Little is known about the identity and mechanism of action of the molecular chaperones that protect osteoblasts and osteocytes from stress-induced cytoskeletal and cellular damage during periods of physiological adaptation.…”
Section: Introductionmentioning
confidence: 99%